Management of Gestational Diabetes Mellitus: Knowledge, Attitudes, and Practices of Obstetric Doctors in Benghazi, Libya - Mohamed, Hisham Yacoub; Buzaid, Najat Omer; Eljazwi, Imhemed A. (Ibnosina Journal of Medicine and Biomedical Sciences, 2024)
Introduction Gestational diabetes mellitus (GDM) adversely affects the mother and fetus. Its diagnosis and management are of great importance to prevent complications. Mothers with GDM are at great risk of developing type 2 diabetes, and metabolic changes can persist for 3 years postdelivery. We assessed the knowledge and practice of obstetricians working at Benghazi Medical Centre (BMC) regarding gestational diabetes.Materials and Methods A cross-sectional descriptive study was conducted at the obstetric department of BMC; we included all postgraduate doctors in July 2021 in the study. The questionnaire included demographic data and questions related to knowledge regarding the definition of GDM, diagnosis, and complications to the mother and fetus. It also included practices toward GDM, including screening, management, follow-up, and postpartum screening for diabetes.Results The total number of doctors who agreed to participate was 102, and the response rate was 72.9%. The mean age of the participants was 35.4 ± 7.2 years; most of the studied group were females 97 (95.1%), 76 (74.5%) were senior house officers, 16 (15.7%) were mid-grades, and 10 (9.8%) were seniors. Most working obstetricians, 76 (74.5%), had less than 10 years of experience. One hundred (98%) participants heard about GDM, and only 39 (38.2%) correctly defined GDM. Regarding the threshold for fasting glucose to diagnose GDM, only 11 (10.8%) gave a right answer of 92 mg/dL. Most participants had a good knowledge of GDM risk factors and complications. Regarding follow-up, only 35 (34.3%) participants provided the correct answer, and only 27 (26.5%) mentioned insulin as the medical treatment of choice.Conclusion Although most of our studied group had contact with GDM patients, most needed basic knowledge regarding definition, diagnosis, and screening. Different opinions regarding diagnostic thresholds and management practices were observed. We recommended the establishment of a gestational diabetes clinic with the cooperation of endocrinologists and obstetricians, as well as local guidelines.
Keywords: gestational diabetes; knowledge; Benghazi; obstetricians